PERANAN SATUAN LALU LINTAS POLISI RESORT DALAM PELAYANAN ADMINISTRASI SURAT TANDA NOMOR KENDARAAN (Studi di Kantor Bersama Sistem Administrasi Manunggal Satu Atap Sangihe) - MAKAMINAN, YULIKE; Posumah, Johnny Hanny; Pombengi, Jericho Danga (JURNAL ADMINISTRASI PUBLIK, 2016)
ABSTRACK : Based on the research results, it can be concluded that the role of Satlantas Polres in the administrative service of STNK in Samsat Sangihe Joint Office in general can be done well, but it is not fully demonstrating the principles of Prime Regident Ranmor service yet as stipulated in the Regulation of Chief of Police Number 5 Year 2012, which are simple, fast, accurate, accountable, informative, and convenient. Based on the conclusion of the research result, it is suggested that the principles of simple, fast, accurate, accountable, informative, and convenient services can be improved in the administrative service of STNK by Satlantas Polres in Samsat Sangihe Joint Office. Therefore, some actions that is needed to be done, among other things is to add the number of personnel officers, to improve the infrastructures and facilities and to add facilities in serving. Keywords: Role of Satlantas, STNK Service